Validation of the Indonesian version of the Kansas city cardiomyopathy questionnaire in heart failure patients - Syifa Mahmud Syukran Akbar; Habibie Arifianto; Heru Sulastomo; Niniek Purwaningtyas; Ahmad Yasa; Ari Natalia Probandari; Khusnun Alifah (Heart Science Journal, 2026)
BACKGROUND: Heart failure is one of the leading contributors to morbidity and mortality globally, and it has a significant impact on patients' quality of life. Accurate assessment of health-related quality of life (HRQoL) is essential in the management of heart failure patients; however, measurement tools in the local language remain limited. OBJECTIVES: The purpose of this study was to validate the Kansas City Cardiomyopathy Questionnaire (KCCQ) among Indonesian patients suffering from heart failure. METHODS: This study was an analytic observational cross-sectional study conducted from July to August 2023 at the cardiology outpatient clinics of UNS Hospital and Dr. Moewardi Hospital, Central Java. The adaptation process included forward-backward translation and preliminary testing. Validity was evaluated using Pearson correlation, and reliability was measured with Cronbach’s alpha. RESULTS: A total of 115 heart failure patients were included in this study. All 23 items in the Indonesian version of the KCCQ showed strong correlation values (r ≥ 0.154; p < 0.001) and excellent internal consistency (Cronbach’s alpha = 0.933). Domain analysis also demonstrated high reliability across all subscales. The KCCQ score had a strong negative correlation with the NYHA classification (r = -0.713; p < 0.001), but a weak and non-significant correlation with LVEF (r = 0.156; p = 0.097). CONCLUSION: The Indonesian version of the KCCQ is valid and reliable for assessing health-related quality of life in patients with heart failure.